Factors influencing lecturers’ retention in a South African university - Mahoko, Neo (University of the Free State, 2023)
Most university first-year students do not get an opportunity to graduate in the presence of their first-year lecturers because their lecturers would have moved to another university. The identified challenge for this study is that universities cannot retain their lecturers. The question now is why are they are failing to retain their lecturers for longer. The research question was formulated from the research problem, i.e., what factors influence the lecturers’ retention in a South African University? Subsequently, the aim of the study was formulated as the focus was on exploring factors influencing lecturers’ retention in a South African University. The qualitative research approach was chosen for collecting and analysing the data. The University stakeholders are the population, and the sample consists of fourteen participants. That is six lecturers with more than three years of working experience, four Human Resource Management (HRM) staff and four Deans/Heads of Departments (HoDs). Sampling was done using three forms of selection: purposive, convenient and snowball. As a result, a rural campus in South Africa was selected as the research site. The above-mentioned participants were interviewed by means of semi-structured interviews as a method of collecting data. Thereafter, Braun and Clarke’s six-step thematic analysis method was adopted for analysing the data with the use of the themes. Once the data was analysed and interpreted, the findings were as follows: universities are not providing a conducive work environment for teaching and learning. Additionally, as minor as it may seem, poor internet connection is a major challenge for lecturers. The excellence awards ceremony and incremental payments resulting from outstanding performance should be implemented as part of the reward systems. One of the recommendations for universities is to build housing units for lecturers on campus. Consequently, it will have a competitive advantage when the university can retain its lecturers by satisfying their needs. As a result, stakeholders such as HRM staff will focus on other matters than always filling the lecturers’ vacancies, and students will have the first-year lecturers present at their graduation ceremony. In addition, there will be a rich pool of experienced supervisors to guide the post-graduate students from the beginning until the end.
Dissertation (M.Ed.(Education Management and Leadership))--University of the Free State, 2023
Keywords: Retention; University lecturers; Rural campus